2022
DOI: 10.1515/opis-2022-0129
|View full text |Cite
|
Sign up to set email alerts
|

Improving the usefulness of research data with better paradata

Abstract: Considerable investments have been made in Europe and worldwide for developing research data infrastructures. Instead of a general lack of data about data, it has become apparent that a pivotal factor that drastically constrains data use is the absence of contextual knowledge about how data was created and how it has been curated and used. This applies especially to many branches of social science and humanities research, where data is highly heterogeneous, both by its kind (e.g. being qualitative, quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…, 2016), often suffer from methodological deficiencies and technical hindrances (cf. Huvila, 2022, p. 30) and are “(…) embedded in a local context, which makes it difficult for reusers to understand and trust the data” (Faniel and Zimmerman, 2011, p. 60). Reciprocally, “[t]he same factors that make it hard for scientists to reuse data collected by those from a different community also make it difficult for data producers to share data” (Faniel and Zimmerman, 2011, p. 61).…”
Section: The Issue Of Un-fair-nessmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2016), often suffer from methodological deficiencies and technical hindrances (cf. Huvila, 2022, p. 30) and are “(…) embedded in a local context, which makes it difficult for reusers to understand and trust the data” (Faniel and Zimmerman, 2011, p. 60). Reciprocally, “[t]he same factors that make it hard for scientists to reuse data collected by those from a different community also make it difficult for data producers to share data” (Faniel and Zimmerman, 2011, p. 61).…”
Section: The Issue Of Un-fair-nessmentioning
confidence: 99%
“…Reciprocally, “[t]he same factors that make it hard for scientists to reuse data collected by those from a different community also make it difficult for data producers to share data” (Faniel and Zimmerman, 2011, p. 61). No wonder that “data reuse is not (…) as widespread as it might be imagined (…)” (Huvila, 2022, p. 30). Yet at the same time, “[t]here is almost universal agreement that scientific data should be shared for use beyond the purposes for which they were initially collected” (Faniel and Zimmerman, 2011, p. 59) and within the digital humanities there have been repeated calls to embrace the “data deluge” (e.g.…”
Section: The Issue Of Un-fair-nessmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the results of the on-going ERCfunded project CAPTURE indicated that the lack of interoperability of archaeological data and information may be the outcome of techno-politics. To that end, the paradata, namely the creation method of digital research outputs, are receiving further attention [36,37].…”
Section: Studying Digital Legaciesmentioning
confidence: 99%